Design optimization of quasi-active gate control for series-connected power devices - Teerakawanich, Nithiphat; Johnson, Christopher Mark (Institute of Electrical and Electronics Engineers, 2014)
This paper presents a new gate drive circuit for driving a series string of IGBTs. The proposed quasi active gate control (QAGC) circuit is simple to implement as it composes of only a few passive components in addition to a standard gate driver. No separate isolation power supply is required for the upper devices in the stack. The proposed QAGC circuit provides an effective way to drive the power devices and control static and dynamic voltage sharing to the devices at the same time. The theoretical switching operation and the oscillation stability analysis allow criteria for component selection to be established. Limitations of the QAGC circuit is also identified. The modification of the circuit to support more power devices in the series stack is discussed with the aid of the simulation results. The switching operation of the circuit is validated from the experimental results using 2 IGBTs connected in series. The circuit shows a satisfied switching operation with well-controlled dynamic and static voltage sharing and comparable gate voltage between the coupled devices.